N-glycosylation enables high lateral mobility of GPI-anchored proteins at a molecular crowding threshold - Hartel, Andreas J. W.; Glogger, Marius; Jones, Nicola G.; Abuillan, Wasim; Batram, Christopher; Hermann, Anne; Fenz, Susanne F.; Tanaka, Motomu; Engstler, Markus (Nature Communications, 2016)
How molecular crowding affects membrane protein diffusion and function is not known. Here the authors measure diffusion of variant surface glycoprotein on trypanosomes and discover a molecular crowding threshold that limits diffusion, and find that N-linked glycans help to prevent retarding intermolecular interactions.
Gesehen am 30.04.2020